(untitled) (Community Based Medical Journal, 2016)
Various forms of skin disease like psoriasis have been found to show disturbances in systemic calcium metabolism in some cases. Calcium is the major regulator of keratinocytes differentiation. The main objective of this study was to find out the serum calcium level of patients with psoriasis in comparison with control subjects without psoriasis. The present study was a case control study from July 2015 to June 2016. Consecutive type of sampling method was followed in this study. The case group was consisting of 30 psoriatic patients and the control group was consisting of 30 non psoriatic patients attended in Skin and VD department of Dhaka Medical College Hospital (DMCH) and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. The mean age of the psoriatic group was 35.57±7.75 years (minimum 22 years and maximum 50 years), while it was 35.17±7.32 years (minimum 23 years and maximum 48 years) in the control group. The mean serum calcium level in psoriatic patients was 8.84±0.95 mg/dl (minimum 7.2mg/dl and maximum 10.2 mg/dl) while in controls it was 9.49±0.90 mg/dl (minimum 7.7 mg/dl and maximum 10.9 mg/dl). Statistical difference was observed between case and control participants with p-value <0.05. Hypocalcemia was observed in 33.33% psoriatic patients as compared 10% in controls (P value <0.05). In conclusion, serum calcium levels were lower in psoriatic patients than in control subjects. It is better to include dairy foods as calcium resource in daily diet of patients suffering from psoriasis. CBMJ 2016 July: Vol. 05 No. 02 P: 29-32